Mycocidal effect of plant-based essential oil on rice brown spot / sesame leaf spot incited by Bipolaris oryzae (Breda de Haan) Shoemaker - Kamali, P; Jaiganesh, V; Devayani, N; Sundaramoorthy , S; Kannan, C; Theradimani, M; Sheela, J; Rajinimala, N; Sudha, R K R; Ranjith, R R S (Plant Science Today, 2025)
The present research work was assumed to inspect the effect of essential oils used for biological management of sesame leaf spot / rice brown spot caused by B. oryzae (Breda de Haan) Shoemaker. The essential oils viz., cinnamon oil, clove oil, citronella oil, thyme oil and rosemary oil were examined in different concentrations against B. oryzae under in vitro conditions. The results revealed that, citronella oil was found to be more effective against brown spot pathogen and completely inhibited the mycelial growth even at 2 % concentration onwards. Whereas in field conditions, citronella oil @ 0.2 % showed minimum disease incidence which is statistically on par with the fungicide difenoconazole (0.2 %). GC - MS analysis was conducted to identify the chemical compounds present in citronella oil, revealing a total of 60 different compounds. Among them linalyl acetate, geraniol, eugenol and geranyl acetate were identified as antimicrobial secondary metabolites. FT-IR analysis exhibited a characteristic peak at 2924.40 cm-1, corresponding to C-H stretching, typically observed within the 2850-2950 cm-1 range. This indicates the aliphatic nature of the hydrocarbons present in citronella oil. Based on the metabolomic analysis, the bioactive compounds and aliphatic hydrocarbons in citronella oil may contribute to suppressing rice brown spot or sesame leaf spot disease and enhancing biometric attributes.